(3GddeYI GdeGQOjfjI aj TQM GdjGSejfjIs - (3eMeO Hf eMeO Hf CMeO GdZRGd GdOeTbqj, HOQ GdOjf, GdTgjQ HSHW GdeGQOjfj , J (B912 (3g` s; (3CHh eMeO Hf YHO Gddg Hf MLGL Hf GdjGSejfjs ((3eMeO eci GdWfHGQi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi CMUi cd TF YOOkG s
(3BNQgG (B:s
(3hgPG BNQ eG bUOfGg ef GdJYdjb Ydi gPg GdCQLhRI s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B215 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA QjGVjGJ (B- (3bSe (B3 - (3U (B79 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B62s
Keywords: (3GdQjGVjGJs